Workshop Penulisan Penelitian Tindakan Kelas (PTK) Bagi Guru Smp Negeri 2 Majene: - - Ruslan; Umar; Intan, Intan Fandini (Universitas Muhammadiyah Malang, 2023)
Purpose – The aim of this activity is to provide teachers with an overview of how to make a PTK and how to compile a PTK in the form of a scientific article. Design/methodology/approach – Service activities in the form of classroom Action Research (PTK) writing workshops were carried out at SMP Negeri 2 Majene. The implementation of PTK writing uses the blended learning method, which combines two types of methods, namely training carried out face-to-face with participants and training held online. The blended learning method was chosen to provide diverse training and adapt to the needs of teachers. It is hoped that this workshop can improve teachers' skills in writing PTK and help improve teacher professionalism. Findings – The results obtained, namely the evaluation before and after the activity, contained very significant differences. Before the activity, there were no participants who answered that they really knew for each question and most of the participants answered that they didn't know and very don't know, whereas after the activity there were no participants who answered that they didn't know and really didn't know for each question. The participants were very enthusiastic about the PTK training provided because this training could provide very extensive information regarding how to prepare a good PTK. Originality/value – Writing PTK is something that must be produced by teachers when proposing a promotion so that teachers must be able to write PTK in accordance with the rules for writing good and correct PTK, with this training teachers are greatly helped.